1994
DOI: 10.1002/1097-0142(19941215)74:12<3083::aid-cncr2820741204>3.0.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

Nasopharyngeal lymphoid tissue masses in patients with human immunodeficiency virus-1. Histologic findings and clinical correlation

Abstract: Background. Although the histologic changes in lymph nodes in patients infected with the human immunodeficiency virus‐1 (HIV‐1) are well described, the histology and resulting clinical symptoms of hyperplastic nasopharyngeal lymphoid tissue (NPLT) in these patients are not widely known, particularly to pathologists and oncologists. Methods. Nine patients with HIV‐1 presented with a nasopharyngeal mass, nasal stuffiness, nasal bleeding, hearing loss, and cervical lymphadenopathy in various combinations. Tonsill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…In a report by Barzan et al [7], 80% of 36 HIV-positive patients had pathologically confirmed nasopharyngeal lymphatic tissue hypertrophy. Most published observations suggested that nasopharyngeal lesions in HIV-infected patients were reactive and represented follicular hyperplasia [8, 9], but malignant lesions were also reported in nasopharyngeal lesions of patients with HIV infection [10]. There was a case report about malignant transformation of nasopharyngeal lymphoid hypertrophy [11].…”
Section: Discussionmentioning
confidence: 99%
“…In a report by Barzan et al [7], 80% of 36 HIV-positive patients had pathologically confirmed nasopharyngeal lymphatic tissue hypertrophy. Most published observations suggested that nasopharyngeal lesions in HIV-infected patients were reactive and represented follicular hyperplasia [8, 9], but malignant lesions were also reported in nasopharyngeal lesions of patients with HIV infection [10]. There was a case report about malignant transformation of nasopharyngeal lymphoid hypertrophy [11].…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of nasopharyngeal carcinoma is based on a maintained high-level clinical suspicion and is obtained with clinical (ear, nose, and throat) and fiberoptic examination, and appropriate radiological imaging: CT and magnetic resonance imaging scans are complementary for the initial screening, whereas PET technique proves more effective for the clinical follow-up and the early detection of eventual relapses. 6,12 However, a prompt local biopsy is mandatory to examine the histopathologic picture and to J INT ASSOC PHYSICIANS AIDS CARE 6(4); 2007 study eventual cell transformation, 5,[12][13][14][15] as well as to detect the presence of EBV genoma, 1,6,10,12 as mentioned above. In an immunocompromised host or among HIV-infected patients, the differential diagnosis of nasopharyngeal carcinoma has to take into account a broad spectrum of bacterial, fungal, mycobacterial, and other opportunistic infections, and lymphoma and other malignancies too, 12,16,17 while a concomitant, EBV-associated lymphatic hypertrophy of surrounding tissues may be more frequent just in patients with HIV disease, to mimic a lymphoproliferative disease.…”
Section: Discussionmentioning
confidence: 99%
“…17 Castleman's syndrome, initially associated with EBV too, includes multicenter proliferative disorders that seem to be more frequently associated with other herpes viruses (ie, HHV-8). 18 In fact, among HIVinfected patients, EBV-associated lymphoproliferative disorders and malignant lymphomas are known to be proportionally more frequent than in the general population, 1,5,[13][14][15] but a diagnosis of AIDS may be posed only when Burkitt lymphoma or primary brain lymphoma are of concern. In about one half of AIDSrelated non-Hodgkin lymphomas, the expression of EBV antigen may be found by a wide range of histopathological studies, thus resembling the situation of African Burkitt lymphoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Does hyperplastic nasopharyngeal lymphoid tissue (NPLT) in human immunodeficiency virus-1 (HIV- 1) infection deserve greater attention?…”
Section: Correspondence Nasopharyngeal Lymphoid Tissue Masses In Patimentioning
confidence: 99%